Self-management behaviors in World Trade Center rescue and recovery workers with asthma. (3rd April 2019) - Rojano, Belen; West, Erin; Goodman, Emily; Weiss, Jeffrey J.; de la Hoz, Rafael E.; Crane, Michael; Crowley, Laura; Harrison, Denise; Markowitz, Steven; Wisnivesky, Juan P.
ABSTRACT: Background : Asthma is a major source of morbidity among World Trade Center (WTC) rescue and recovery workers. While physical and mental health comorbidities have been associated with poor asthma control, the potential role and determinants of adherence to self-management behaviors (SMB) among WTC rescue and recovery workers is unknown. Objectives : To identify modifiable determinants of adherence to asthma self-management behaviors in WTC rescue and recovery worker that could be potential targets for future interventions. Methods : We enrolled a cohort of 381 WTC rescue and recovery workers with asthma. Sociodemographic data and asthma history were collected during in-person interviews. Based on the framework of the Model of Self-regulation, we measured beliefs about asthma and controller medications. Outcomes included medication adherence, inhaler technique, use of action plans, and trigger avoidance. Results : Medication adherence, adequate inhaler technique, use of action plans, and trigger avoidance were reported by 44%, 78%, 83%, and 47% of participants, respectively. Adjusted analyses showed that WTC rescue and recovery workers who believe that they had asthma all the time (odds ratio [OR]: 2.37; 95% confidence interval [CI]: 1.38–4.08), that WTC-related asthma is more severe (OR: 1.73; 95% CI: 1.02–2.93), that medications are important (OR: 12.76; 95% CI: 5.51–29.53), and that present health depends on medications (OR: 2.39; 95% CI: 1.39–4.13) were more likely to be adherent to their asthma medications. Illness beliefs were also associated with higher adherence to other SMB. Conclusions : Low adherence to SMB likely contributes to uncontrolled asthma in WTC rescue and recovery workers. Specific modifiable beliefs about asthma chronicity, the importance of controller medications, and the severity of WTC-related asthma are independent predictors of SMB in this population. Cognitive behavioral interventions targeting these beliefs may improve asthma self-management and outcomes in WTC rescue and recovery workers. Key message : This study identified modifiable beliefs associated with low adherence to self-management behaviors among World Trade Center rescue and recovery rescue and recovery workers with asthma which could be the target for future interventions. Capsule summary : Improving World Trade Center-related asthma outcomes will require multifactorial approaches such as supporting adherence to controller medications and other self-management behaviors. This study identified several modifiable beliefs that may be the target of future efforts to support self-management in this patient population.